2020
DOI: 10.1108/jabs-06-2019-0189
|View full text |Cite
|
Sign up to set email alerts
|

Does environmental concern drive Asian firms’ governance?

Abstract: Purpose The sustainability issues faced by Asian firms, such as environmental destruction and depletion of resources, require the existing corporate social responsibility (COSR) models to be carefully examined and re-conceptualized. Both researchers and practitioners have indicated how social equity and having a long-term business perspective are imperative to address environmental concerns alongside fulfilling the wealth maximization goals among firms. The purpose of this study is to contribute to the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 122 publications
(134 reference statements)
0
16
0
Order By: Relevance
“…The existing contributions and reviews in this field can be classified into two main categories. On one side, we find general contributions that do not focus on a specific country or industry, and which therefore provide broad observations, e.g., Ahmadi et al, Ebinger and Omondi [8,9]; on the other side, there are studies focused on a single geographical area or industrial sector which provide specific-but not always generalizable-insights, e.g., Mitra and Gaur, Giuffrida et al [10,11]. This study aims to bridge these two opposing clusters of contributions by reuniting them in the same review paper that specifically addresses sustainability in different settings.…”
Section: Introductionmentioning
confidence: 66%
“…The existing contributions and reviews in this field can be classified into two main categories. On one side, we find general contributions that do not focus on a specific country or industry, and which therefore provide broad observations, e.g., Ahmadi et al, Ebinger and Omondi [8,9]; on the other side, there are studies focused on a single geographical area or industrial sector which provide specific-but not always generalizable-insights, e.g., Mitra and Gaur, Giuffrida et al [10,11]. This study aims to bridge these two opposing clusters of contributions by reuniting them in the same review paper that specifically addresses sustainability in different settings.…”
Section: Introductionmentioning
confidence: 66%
“…Sustainability reports tend to indicate actual sustainability performance of companies and therefore have business implications (Papoutsi and Sodhi, 2020). It is essential to re-model the current corporate social responsibility framework among Asian firms which do not have proper guidelines to achieve environmental and social performances (Mitra and Gaur, 2020). When demand-enhancing effects outweigh the cost-increasing effects, then the firm is observed to make investment in sustainable technologies (Veldman and Gaalman, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Albuquerque et al (2020) observed that stocks with higher environmental and social characteristics perform better in terms of returns, volatility, and operating profit margins during the COVID-19 market crash. Because of this, practitioners, policy makers, academicians and other interest groups see a need in re-evaluating the post-modern world economy (Mitra and Gaur, 2020; Singh et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%